Attitude of Foreign Language Learners on Nonverbal Communication and Privacy in Communicative Classes - Nemati, Azedah (Vision: Journal for Language and Foreign Language Learning, 2019)
Communication has verbal and nonverbal aspects.It has been estimated that 82% of class communication is nonverbal. While the role of nonverbal behavior in English classes is much it is hitherto an unexplored area. One subpart of nonverbal communication is proxemics or space. Combing nonverbal communication and the right to privacy, this article is aimed at exploring the attitude of foreign language students regarding nonverbal communication and privacy right in English classes. A nonverbal questionnaire along with privacy proposed by the researcher was answered by 107 general English participants. Based on their opinion the major findings were that students like, smiling, tidy and on time teachers who explain and illustrate in English classes. However, they do not like to answer questions regarding their personal life such as personal description, identification, health or background. As a result, their privacy right should be observed in communicative English classes.